PEMBELAJARAN BERBASIS PERMAINAN TRADISIONAL UNTUK MENGEMBANGKAN POTENSI BAHASA DAN SOSIOEMOSIONAL ANAK DI TAMAN KANAK-KANAK - Wiwik Pudjaningsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Writing this article is to explain "traditional game-based learning to develop the potential of language and socioemotional early childhood", particularly of children aged 5-6 years (kindergarten). To that end, the description in this article include: learning in early childhood education, the development potential and the socio-emotional language in kindergarten, and the implementation of the traditional game based learning in kindergarten. The first description includes a foothold learning in early childhood education and a theme-based learning, based learning centers, the traditional games in early childhood education. The second description covers the scope of language and socio-emotional development of children and the level of achievement of language and socio-emotional development of children. The third description includes the scope of application of the language and socio-emotional development of the child, the application-based learning centers, approach of learning theme, and the application of traditional games in learning.Keywords: learning, traditional game, language, socio-emotional